Strategy for IT-Business Alignment in a Higher Education Institution Using Initial Fit-HR Model - Fitroh Fitroh; Zulfiandri Zulfiandri; Isnaini Monita Safitri; Puji Rahayu; Amany Burhanuddin Umar Lubis; Rohadatul Aisy; Mohammed Ikhlayel (Applied Information System and Management (AISM), 2022)
IT-business alignment (ITBA) is the development of a Strategic Alignment Model (SAM), which was introduced some decades ago, and is still the most critical issue for top management. This study proposes the Initial FIT-HR model in mapping specific components indicators that align HR in carrying out business processes for higher education institutions (HEI) in Indonesia. Previously, research had studied the alignment of HR management with IT to suit the Tri Dharma of Higher Education towards World-Class University. Meanwhile, the methodology used a mixed-method (with interview techniques, questionnaires, and focus group discussion FGD), which went through 3 phases: identification and determination of indicators, the initial design phase of the model, and validation. The results after the FGD process showed that four indicators (out of 40 based on 20 papers) were invalid in mapping specific components due to the different opinions of the participants. Therefore, in future work, the Islamic concepts to the proposed modeling. In addition, this study produced an initial model that collaborated the BITA concept with tree science as an approach to be applied by the higher education industry.